Is there a role for absorbable metals in surgery? A systematic review and meta-analysis of Mg/Mg alloy based implants - Sukotjo, Cortino; Lima-Neto, Tiburtino J. [UNESP]; Júnior, Joel Fereira Santiago; Faverani, Leonardo P. [UNESP]; Miloro, Michael (MDPI, 2020)
Magnesium (Mg) alloys have received attention in the literature as potential biomaterials for use as absorbable implants in oral and maxillofacial and orthopedic surgery applications. This study aimed to evaluate the available clinical studies related to patients who underwent bone fixation (patients), and received conventional fixation (intervention), in comparison to absorbable metals (comparison), in terms of follow-up and complications (outcomes). A systematic review and meta-analysis were performed in accordance with the PRISMA statement and PROSPERO (CRD42020188654), PICO question, ROBINS-I, and ROB scales. The relative risk (RR) of complications and failures were calculated considering a confidence interval (CI) of 95%. Eight studies (three randomized clinical trial (RCT), one retrospective studies, two case-control studies, and two prospective studies) involving 468 patients, including 230 Mg screws and 213 Titanium (Ti) screws, were analyzed. The meta-analysis did not show any significant differences when comparing the use of Mg and Ti screws for complications (p = 0.868). The estimated complication rate was 13.3% (95% CI: 8.3% to 20.6%) for the comparison group who received an absorbable Mg screw. The use of absorbable metals is feasible for clinical applications in bone surgery with equivalent outcomes to standard metal fixation devices.
Keywords: Absorbable implants; Bone surgery; Magnesium (Mg); Oral and maxillofacial; Orthopedic; Titanium (Ti)